2019
DOI: 10.48550/arxiv.1912.02858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Settling the relationship between Wilber's bounds for dynamic optimality

Abstract: In FOCS 1986, Wilber proposed two combinatorial lower bounds on the operational cost of any binary search tree (BST) for a given access sequence X ∈ [n] m . Both bounds play a central role in the ongoing pursuit of the dynamic optimality conjecture (Sleator and Tarjan, 1985), but their relationship remained unknown for more than three decades. We show that Wilber's Funnel bound dominates his Alternation bound for all X, and give a tight Θ(lg lg n) separation for some X, answering Wilber's conjecture and an ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…We show that, for the sequence X given by Theorem 1.1, WB (2) (X) ≥ Ω(n log log n) holds, and therefore WB (2) (X)/WB(X) ≥ Ω(log log n/ log log log n) for that sequence, implying that the gap between WB(X) and WB (2) (X) may be as large as Ω(log log n/ log log log n). We note that we only realized that our results provide this stronger separation between the two Wilber bounds after hearing the statements of the results from the independent work of Lecomte and Weinstein [LW19] mentioned above.…”
Section: Negative Results For Wb-1 and Its Extensionsmentioning
confidence: 63%
See 2 more Smart Citations
“…We show that, for the sequence X given by Theorem 1.1, WB (2) (X) ≥ Ω(n log log n) holds, and therefore WB (2) (X)/WB(X) ≥ Ω(log log n/ log log log n) for that sequence, implying that the gap between WB(X) and WB (2) (X) may be as large as Ω(log log n/ log log log n). We note that we only realized that our results provide this stronger separation between the two Wilber bounds after hearing the statements of the results from the independent work of Lecomte and Weinstein [LW19] mentioned above.…”
Section: Negative Results For Wb-1 and Its Extensionsmentioning
confidence: 63%
“…Independent Work. Independently from our work, Lecomte and Weinstein [LW19] showed that Wilber's Funnel bound (that we call WB-2 bound and discuss below) dominates the WB-1 bound, and moreover, they show an access sequence X for which the two bounds have a gap of Ω(log log n). In particular, their result implies that the gap between WB(X) and OPT(X) is Ω(log log n) for that access sequence.…”
mentioning
confidence: 62%
See 1 more Smart Citation